2021
DOI: 10.3389/fmicb.2021.561863
|View full text |Cite
|
Sign up to set email alerts
|

Differential Packaging Into Outer Membrane Vesicles Upon Oxidative Stress Reveals a General Mechanism for Cargo Selectivity

Abstract: Selective cargo packaging into bacterial extracellular vesicles has been reported and implicated in many biological processes, however, the mechanism behind the selectivity has remained largely unexplored. In this study, proteomic analysis of outer membrane (OM) and OM vesicle (OMV) fractions from enterotoxigenic E. coli revealed significant differences in protein abundance in the OMV and OM fractions for cultures shifted to oxidative stress conditions. Analysis of sequences of proteins preferentially packaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 76 publications
2
24
0
Order By: Relevance
“…As the need for vesicle purification has been recognized and the purification techniques have improved (for recent reviews, see Bonnington & Kuehn, 2014Elhenawy et al, 2016;Orench-Rivera & Kuehn, 2021) does not mimic the composition of the envelope from which they are derived. Indeed, molecular "rules" have been validated that show mechanisms for specific inclusion and exclusion of soluble and membrane-associated OMV cargo based on polypeptide sequence or physical parameters (McBroom & Kuehn, 2007;Orench-Rivera & Kuehn, 2021).…”
Section: Vesicle Cargo Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the need for vesicle purification has been recognized and the purification techniques have improved (for recent reviews, see Bonnington & Kuehn, 2014Elhenawy et al, 2016;Orench-Rivera & Kuehn, 2021) does not mimic the composition of the envelope from which they are derived. Indeed, molecular "rules" have been validated that show mechanisms for specific inclusion and exclusion of soluble and membrane-associated OMV cargo based on polypeptide sequence or physical parameters (McBroom & Kuehn, 2007;Orench-Rivera & Kuehn, 2021).…”
Section: Vesicle Cargo Selectionmentioning
confidence: 99%
“…As the need for vesicle purification has been recognized and the purification techniques have improved (for recent reviews, see (Prados‐Rosales et al , 2014a; Klimentová & Stulík, 2015; Tulkens et al , 2020a; Liangsupree et al , 2021; Nasukawa et al , 2021)), analysis of vesicle cargo has revealed export selectivity, a hallmark of a bona fide secretory process. Numerous quantitative proteomic and lipidomic analyses have demonstrated that the composition of OMVs (McMahon et al , 2012; Bonnington & Kuehn, 2014, 2016; Elhenawy et al , 2016; Orench‐Rivera & Kuehn, 2021) does not mimic the composition of the envelope from which they are derived. Indeed, molecular “rules” have been validated that show mechanisms for specific inclusion and exclusion of soluble and membrane‐associated OMV cargo based on polypeptide sequence or physical parameters (McBroom & Kuehn, 2007; Orench‐Rivera & Kuehn, 2021).…”
Section: Introduction: a Paradoxmentioning
confidence: 99%
See 3 more Smart Citations